2016
DOI: 10.1017/s1751731115001834
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: mesenchymal progenitor cells in intramuscular connective tissue development

Abstract: The abundance and cross-linking of intramuscular connective tissue contributes to the background toughness of meat, and is thus undesirable. Connective tissue is mainly synthesized by intramuscular fibroblasts. Myocytes, adipocytes and fibroblasts are derived from a common pool of progenitor cells during the early embryonic development. It appears that multipotent mesenchymal stem cells first diverge into either myogenic or non-myogenic lineages; non-myogenic mesenchymal progenitors then develop into the strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 107 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…Besides, the abundance of PDGFRA in finishing Angus is correlated with its higher IMF contents when compared with Nellore (Martins et al, 2015). Thus PDGFRA is a marker of intramuscular adipocyte progenitors in beef cattle (Huang et al, 2012a;Miao et al, 2016). In pigs, PDGFRA þ cells are located in the gaps of myofibers in longissimus dorsi muscle, and more PDGFRA þ cells are detected in longissimus dorsi muscle of fat-type pigs compared with that of lean-type pigs at 180 days of age (Sun et al, 2017), albeit no difference was observed in the abundance of PDGFRA þ cells or PDGFRA expression between longissimus thoracis (with higher IMF contents) and semitendinosus muscle (with lower IMF) in 180-day-old pigs (Chen et al, 2019).…”
Section: Molecular Markers and Heterogeneity Of Fibro-adipogenic Progmentioning
confidence: 93%
See 2 more Smart Citations
“…Besides, the abundance of PDGFRA in finishing Angus is correlated with its higher IMF contents when compared with Nellore (Martins et al, 2015). Thus PDGFRA is a marker of intramuscular adipocyte progenitors in beef cattle (Huang et al, 2012a;Miao et al, 2016). In pigs, PDGFRA þ cells are located in the gaps of myofibers in longissimus dorsi muscle, and more PDGFRA þ cells are detected in longissimus dorsi muscle of fat-type pigs compared with that of lean-type pigs at 180 days of age (Sun et al, 2017), albeit no difference was observed in the abundance of PDGFRA þ cells or PDGFRA expression between longissimus thoracis (with higher IMF contents) and semitendinosus muscle (with lower IMF) in 180-day-old pigs (Chen et al, 2019).…”
Section: Molecular Markers and Heterogeneity Of Fibro-adipogenic Progmentioning
confidence: 93%
“…Regulation of the adipogenic differentiation of fibro-adipogenic progenitors Fibro-adipogenic progenitors possess both fibrogenic and adipogenic potentials, and fibrogenesis of intramuscular FAPs has been depicted in our previous review (Miao et al, 2016). Because both adipocytes and fibroblasts are derived from FAPs, it had been postulated that enhancing adipogenic differentiation may correspondingly reduce fibrogenesis.…”
Section: Adipogenic Differentiation Of Fibro-adipogenic Progenitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of LIF (Austin and Burgess, 1991;Nicola and Babon, 2015), heparin-binding epidermal growth factor (hb-EGF) (Thornton et al, 2015), TGFβ (Vitello et al, 2004) and insulin-like growth factor 1 (IGF-1) (Allen and Boxhorn, 1989;Vitello et al, 2004) can improve BSC proliferation. In addition to its central role in muscle development, TGF-β contributes to mature skeletal muscle mass, and is a key regulator of intramuscular fibrogenesis (Kollias and McDermott, 2008;Miao et al, 2016). In addition, it was shown that TGF-β1 suppressed myogenesis in 2D cultures, while enhancing myogenesis in 3D cultures, rendering it a valuable regulator of in-vitro muscle tissue development (Krieger et al, 2018).…”
Section: Satellite Cells and Myogenesismentioning
confidence: 99%
“…The skeletal muscle ECM is responsible for tissue elasticity, generates adhesion points for cell adherence, provides cells with a 3D environment and regulates cell proliferation, differentiation, migration, morphology and alignment via biochemical and biophysical cues (Tse and Engler, 2011;Hausman, 2012;Chaturvedi et al, 2015;Fuoco et al, 2016;Grzelkowska-Kowalczyk, 2016). The ECM composition and roles are not constant, but change during the muscle development in a process called fibrogenesis, in parallel to myogenesis and adipogenesis (Thorsteinsdóttir et al, 2011;Yan et al, 2013;Miao et al, 2016). In addition to its biological roles, the ECM contains nutrients such as proteins (mostly collagens), and glycosaminoglycans [mostly hyaluronic acid (HA)], and affects the tissue texture and the overall quality of the meat (Purslow, 2005;Guo et al, 2015;Duffy et al, 2016;Listrat et al, 2016;Huang et al, 2017).…”
Section: Fibroblasts and Ecmmentioning
confidence: 99%